Comparing total nitrogen and crude protein content of green coffee beans (Coffea spp.) from different geographical origins - Rodrigues, Carla Igreja; Maia, Rodrigo; Máguas, Cristina (Coffee Science - ISSN 1984-3909, 2011)
A combustion - TCD (thermal conductivity detection) elemental analysis method has been applied for the first time for total nitrogen and crude protein determination of 72 green coffee bean samples from 20 different geographic origins distributed over North America, South America, Africa, Asia and Oceania. Crude protein content varied among different coffees from distinct geographic origins. In this study we aimed at applying an elemental analysis method for total nitrogen determination in green coffee and calculation of crude protein content according to AOAC Official Method 992.23. Elemental analysis by combustion - TCD presented itself as a fast, accurate, high precision and reproducible approach (intermediate precision 1.37% RSD; En 0.17) for the determination of the total nitrogen in green coffee.